Combined transposition of internal obturator and superficial gluteal muscles for perineal hernia treatment in dogs: 17 cases (2017‐2020). (1st November 2022) - Carbonell Rosselló, G.; Turner, A.; Macias, C.; Ramírez, J. M.
Abstract : Objectives: To report the results of the combined transposition of the internal obturator muscle and superficial gluteal muscle for perineal hernia treatment in dogs. Materials and Methods: Retrospective case series of dogs treated with this technique from November 2017 to May 2020, including pre‐ and post‐operative clinical findings, outcome and complications. Results: Seventeen dogs were included in the study. Twelve dogs were presented with unilateral perineal hernia and five dogs with bilateral perineal hernias. Mean duration of clinical signs before presentation was 9 months. All perineal hernias were successfully repaired using a transposition of the internal obturator muscle to cover the ventral aspect of the perineal hernia and the superficial gluteal muscle to cover the dorsal aspect of the hernia with minimal tension. All dogs regained normal defecation within 24 hours post‐surgery. Average follow‐up time was 16 months. No recurrence of clinical signs or rectal deviation was observed. Five dogs developed a superficial minor partial necrosis of the T‐shaped incision and two had surgical site infections. Clinical Significance: Perineal herniorrhaphy using a combined transposition of the internal obturator and the superficial gluteal muscles is feasible and offered excellent results in this cohort of dogs. It may be considered as a technique for repairing chronic and extensive unilateral and bilateral perineal hernias.